2013
DOI: 10.1177/1477153513490715
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for a simplified model to evaluate the circadian effects of light sources

Abstract: In order to evaluate the circadian effects of light, an approach based only on a\ud circadian sensitivity function makes it possible to easily obtain efficiency\ud functions and action factors. However, it does not take into account the circadian\ud human response to light stimuli, which is not linear. Non-linear models are more\ud sophisticated and accurate but they are not easy to apply. In this paper a proposal\ud for an easy way to evaluate the potential ‘circadian effects’ of light sources is\ud presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
1
28
0
1
Order By: Relevance
“…These functions vary in terms of their framework and their relative consideration of retinal neurophysiology. 18,[21][22][23][24][25][26] Research to date has primarily focused on the spectral sensitivity of the human circadian system, but it should be noted that exposure duration also has an impact on the amount of light needed to stimulate the circadian system. Early studies by McIntyre et al 27,28 showed that increasing light levels lead to increased melatonin suppression and required shorter durations of exposure for observing significant suppression.…”
Section: Introductionmentioning
confidence: 99%
“…These functions vary in terms of their framework and their relative consideration of retinal neurophysiology. 18,[21][22][23][24][25][26] Research to date has primarily focused on the spectral sensitivity of the human circadian system, but it should be noted that exposure duration also has an impact on the amount of light needed to stimulate the circadian system. Early studies by McIntyre et al 27,28 showed that increasing light levels lead to increased melatonin suppression and required shorter durations of exposure for observing significant suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Bellia`s method declares an excellent match for light sources with correlated color temperature (CCT) from 2500 K to 6500 K and blackbody radiator (color temperature CT from 1000 K to 10 000 K) with Rea`s model [14]. This modification may be very important for consequent research in nonvisual light impact on humans.…”
Section: The Methods For Circadian Response Evaluation According To Bementioning
confidence: 99%
“…Previous experiments mentioned, that not only ipRGC controls the circadian response, but also other photoreceptorsthe rods and cones [13]. Latest researches stated that data from Brainard and Thapan acquired with monochromatic light sources may be inappropriate, because the effect of b-z opposite channel is not included [14]. Brainard and Thapan`s data at around 500 nm are irregular, and the fitting curve shows a discontinuity point.…”
Section: Computational Model For Circadian Responsementioning
confidence: 99%
“…Other figures of merit for the circadian system have been reported such as circadian light value [23][24][25] (CL A ) and melatonin suppression index 26 (MSI) to evaluate the circadian potential of light sources. The MSI shows the potential spectral impact of a lamp SPD on the melatonin suppression.…”
Section: Caf Blm Lmmentioning
confidence: 99%